Implementasi Model Pembelajaran Kooperatif Berbantuan Spinning Question Untuk Meningkatkan Hasil Belajar Kognitif Siswa - Nurhaliza, Siti; Y, Yennita; Fauza, Naila (Innovative: Journal Of Social Science Research, 2024)
The study aims to find out the cognitive learning outcomes of students after using the cooperative learning model assisted by spinning questions and to know the differences between the learning outcome of students with the collaborative learning supported by spin questions and conventional learning on vibration and wave matter. This research is a quasi-experimental class action study with a posttest only control group design design. The researchers conducted research in the full semester of the 2023/2024 academic year involving 40 eighth grade students as research subjects that focused on two classes, including control classes and experimental classes. The tool used to obtain the data is a test of cognitive learning outcomes consisting of 20 elements of a double choice. The results of the study were analyzed descriptively and showed that the cognitive learning outcomes of the students in the experimental class were higher than in the control class and there were differences in learning outcome between the two classes. In experimental classes the average cognitivo learning output was 67,75 (sufficient) compared to 59,25 (less) in control class.